Hubungan Kejadian Kasus Covid 19 Terhadap Pelayanan Maternal Di Puskesmas Kota Banjarmasin Tahun 2020 - isnaniah isnaniah; erni setiawati; mukhtar mukhtar (Politeknik Kementerian Kesehatan Banjarmasin, 2021)
(SARS-COV2) virus. Starting from the Wuhan area, Hubei province, China, which first reported cases of pneumonia with no known cause. The mortality rate for COVID-19 in Indonesia is 8.9%, this figure is the highest in Southeast Asia. As for Banjarmasin, based on data from the Banjarmasin Health Service on June 12, 2020, 812 positive cases of Covid-19 were confirmed, with the addition of 37 new cases and 89 cumulative cases of death. Purpose: To find out the Relationship between the Covid 19 Case and Maternal Services at the Banjarmasin City Health Center in 2020 Methods: This study used an analytic survey method with a cross sectional approach. This study used an analytic survey research design. Results: The relationship between the incidence of Covid 19 cases and maternal services shows the incidence of Covid 19 cases out of 8 cases of Covid 19 who were not exposed to good maternal services as many as 8 cases. Of the 15 Reactive cases, 13 cases were good maternal services and 3 cases of poor service Meanwhile, 1 case that was exposed was less good and 2 cases that got good service. Chi-square test results with a significant rate of α 0.005, obtained p value (value) 0.023, meaning p (value) <0.005, then the results can be concluded that there is a relationship between the incidence of Covid 19 and maternal services. Keywords: Covid 19 cases and maternal services